Russian disinformation in Ecuador's (audiovisual) media - Suing, Abel; Lomas, Pablo (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
Disinformation is multiplied through social networks, and many hoaxes show Russian interests, to the extent that the US and the European Union qualify RT and Sputnik as media outlets for the circulation of false facts. This research aims to identify the disinformation generated by RT and Sputnik related to Ecuador in audiovisual media and social networks. The methodology is qualitative and quantitative, descriptive in scope. It is evident that Russian disinformation is present in the country, especially online. It is important to promote media literacy and open a debate on regulation that promotes freedom of expression.